Rationally designed synthetic protein hydrogels with predictable mechanical properties - Junhua Wu (Nature Portfolio, 2018)
Mechanical properties of protein hydrogels are critical to mimic natural tissue but correlating bulk properties on the molecular level remains challenging. Here the authors show that the hierarchy of crosslinkers and load-bearing modules on a molecular level defines the mechanical properties of the hydrogel.